2012
DOI: 10.1371/journal.pone.0046973
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Triggers Pro-Oncogenic Signaling in Human Breast Mammary Epithelial Cells Partly via Stimulation of MiR-21

Abstract: Dyslipidemia and obesity are primary risk factors for the development of atherosclerosis and are also epidemiologically linked to increased susceptibility to a variety of cancers including breast cancer. One of the prominent features of dyslipidemia is enhanced production of oxidized LDL (ox-LDL), which has been shown to be implicated in key steps of atherogenesis including inflammatory signaling and proliferation of vascular cells. In this study we analyzed the effects of ox-LDL in human mammary epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
0
32
0
1
Order By: Relevance
“…For example, one study showed that the serum oxLDL levels are associated with an increased risk of breast cancer27. Furthermore, oxLDL was reported to trigger proliferative and pro-inflammatory signalling in MCF10A cells partly by stimulation of MiR-2117. In addition, oxLDL (lectin-like) receptor 1 (OLR1), the main receptor for internalization of oxLDL, has been reported to play a major role in tumour growth in xenograft mouse models of breast cancer and is critical for cell transformation92829.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study showed that the serum oxLDL levels are associated with an increased risk of breast cancer27. Furthermore, oxLDL was reported to trigger proliferative and pro-inflammatory signalling in MCF10A cells partly by stimulation of MiR-2117. In addition, oxLDL (lectin-like) receptor 1 (OLR1), the main receptor for internalization of oxLDL, has been reported to play a major role in tumour growth in xenograft mouse models of breast cancer and is critical for cell transformation92829.…”
Section: Discussionmentioning
confidence: 99%
“…Two reports have demonstrated that both D-4F and L-4F significantly reduce tumour growth in xenograft mouse models of ovarian and colon cancer, and this effect is partly brought about by their binding to and removing lysophosphatidic acids1016. Recent data have also shown that internalization of oxidized low-density lipoprotein (oxLDL) by mammary epithelial cells may play a significant role in breast cancer by triggering a variety of proliferative and pro-inflammatory mechanisms17. However, the potential in vivo therapeutic effect of apoA-I or its mimetics on breast cancer has not been studied.…”
mentioning
confidence: 99%
“…However, the proliferative effect of oxLDL was prevented in the C4-2/LOX-1(−) cell model, indicating that this effect is closely related to the activation of the LOX-1 receptor by oxLDL. In this sense, the proliferative effect promoted by oxLDL/LOX-1 has been described in muscle cells, endothelial cells and recently in breast cancer cells through activation pathways that involve p38 (MAPK), p44/42 MAPK, and NF- kB [6], [39]. However, the proliferative effects on prostate cancer cells had not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described interactions among OLR1 and different miRNAs; within them, particularly interesting are hsa‐let7‐g and hsa‐miR‐21 that are expressed mainly in endothelial cells and are associated with the apoptosis regulation.…”
Section: Introductionmentioning
confidence: 99%